EXTRACTION, ISOLATION, CHARACTERIZATION AND PHYTOCHEMICAL SCREENING OF EUPHORBIA BALSAMIFERA LEAF EXTRACT FOR PESTICIDAL ACTIVITY AGAINST CALLOSOBRUCHUS MACULATUS (FUDMA JOURNAL OF SCIENCES, 2025)
Pest infestations of stored agricultural products cause substantial global losses, highlighting the need for ecofriendly alternatives to synthetic pesticides. This study explores the insecticidal potential of Euphorbia balsamifera leaf extracts against Callosobruchus maculatus, a major storage pest. Ethanol was used to obtain the crude extracts which were then fractionated into n-hexane, chloroform, ethyl acetate, methanol, and aqueous fractions. Phytochemical analysis confirmed the presence of bioactive compounds including alkaloids, flavonoids, saponins, and terpenoids. The bioassay was conducted at varying concentrations ranging from 0.5 to 2.5 mg/µL, with each treatment performed in triplicate, and mortality rates were recorded over 72 hours. The n-hexane fraction exhibited the highest insecticidal activity, achieving 87% mortality at the highest concentration of 2.5 mg/µL. Further analysis using FT-IR and GC-MS identified key functional groups and bioactive compounds, including azelaic acid and 1-hexyl-2-nitrocyclohexane, known for their pesticidal properties. These findings suggest that Euphorbia balsamifera leaf extract could serve as natural, biodegradable alternatives to synthetic pesticides for storage pest control, contributing to sustainable pest management in agricultural.
Keywords: Euphorbia Balsamifera; Callosobruchus maculatus; Storage pests; Phytochemical Screening; Bioactive compounds; n-hexane fraction; FT-IR; GC-MS; Sustainable pest control